2021
DOI: 10.4269/ajtmh.20-0985
|View full text |Cite
|
Sign up to set email alerts
|

Where Shared Sanitation is the Only Immediate Option: A Research Agenda for Shared Sanitation in Densely Populated Low-Income Urban Settings

Abstract: Shared sanitation is not currently accepted within the international normative definitions of "basic" or "safely managed" sanitation. We argue that pro-poor government strategies and investment plans must include high-quality shared sanitation as an intermediate step in some densely populated urban areas. User experience must be considered in establishing the definition of high quality. We call for additional research on effective interventions to reach these quality standards and for the development of rigoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Further, in densely populated areas, there may not be space for household-level sanitation of any type. Shared sanitation is a subject of considerable debate but may represent the only near-term sanitation option in some settings (Evans et al, 2017;Heijnen et al, 2014;Tidwell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, in densely populated areas, there may not be space for household-level sanitation of any type. Shared sanitation is a subject of considerable debate but may represent the only near-term sanitation option in some settings (Evans et al, 2017;Heijnen et al, 2014;Tidwell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further, in densely populated areas, there may not be space for household-level sanitation of any type. Shared sanitation is a subject of considerable debate but may represent the only near-term sanitation option in some settings ( Evans et al, 2017 ; Heijnen et al, 2014 ; Tidwell et al, 2020 ). Yet, while shared, onsite systems may fill the growing need for safe sanitation in rapidly expanding urban areas in LMICs, to date, there has been little evidence of their health impacts in these settings.…”
Section: Introductionmentioning
confidence: 99%
“…12,8183 Nevertheless, quality sanitation infrastructure can provide important benefits irrespective of preventing pathogen exposure, particularly in crowded urban settlements. 84,85 For example, previous research found users of MapSan intervention latrines and similar facilities in the same neighborhoods reported reduced disgust and embarrassment about unhygienic conditions and improved perceptions of security and privacy. 86…”
Section: Discussionmentioning
confidence: 99%
“…21 Uncertain land tenure discourages investment inbuilt infrastructure, such as toilets, because it may be removed by landowners. 22,23 This underscores the need for additional research that examines local voices and user experiences pertaining to what constitutes managed shared sanitation. These voices remain conspicuously absent from the process of defining global sanitation standards such as those set by the JMP.…”
Section: Introductionmentioning
confidence: 99%
“…To "elicit the experiences and views of poor people and to incorporate these views into all observations, judgments, and actions" is an essential step toward achieving equitybased global health goals such as the SDGs. 24 In the context of managed shared sanitation, user experiences are required to elucidate the attributes of these facilities, 22 thereby dismantling the dichotomy between safely managed facilities and everything else that in many cases acts as a "straightjacket that alienates worthwhile efforts." 4 Therefore, the purpose of this study was to understand user perspectives on the essential attributes of managed shared sanitation facilities and what role these facilities can play in people's lives.…”
Section: Introductionmentioning
confidence: 99%